2005
DOI: 10.2176/nmc.45.344
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Edaravone, a Free Radical Scavenger, for the Treatment of Acute Lacunar Infarction

Abstract: The effect of edaravone as an inhibitor of ischemic brain damage in addition to routine treatment was retrospectively examined in 70 patients with lacunar infarction who were admitted within 24 hours of symptom onset. Clinical status was assessed using the National Institutes of Health Stroke Scale (NIHSS). The modified Rankin Scale (MRS) was used to assess clinical outcomes at 3 months after onset, with a good outcome defined as MRS score Ã2. Risk factors were also evaluated, including evidence of hypertensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…A previous study on 70 patients of acute lacunar infarction had similarly shown that administration of this drug improves the functional outcome in these patients [64].…”
Section: Reactive Oxygen Speciesmentioning
confidence: 82%
“…A previous study on 70 patients of acute lacunar infarction had similarly shown that administration of this drug improves the functional outcome in these patients [64].…”
Section: Reactive Oxygen Speciesmentioning
confidence: 82%
“…The free radical scavenger, edaravone, is the first neuroprotective agent approved by the Japanese Ministry of Health and Welfare for clinical use. Although a randomized, placebo-controlled, double-blind study conducted at multiple centers in Japan showed the efficacy of edaravone in acute cerebral infarction (3), the clinical trials are few (4)(5)(6) (9). Although there were no significant differences in NIHSS on admission and NIHSS at discharge in the two groups, NIHSS on admission was slightly larger and NIHSS at discharge was smaller in the edaravone group.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that edaravone use improved the outcome of the patients with lacunar infarction. 14) We think that edaravone is also useful for the treatment of patients with cardiogenic embolism. In addition, edaravone is expected to extend the therapeutic time window for thrombolytic therapy by protecting endothelial cells and neurons.…”
Section: Discussionmentioning
confidence: 99%
“…1) Edaravone was apparently efficacious in patients with acute ischemic stroke, 7,14) and protected vascular endothelial cells and neurons during acute brain ischemia. 22) EPC-K1, another free radical scavenger, combined with heparin dramatically reduced heparin-induced hemor- Fig.…”
Section: Introductionmentioning
confidence: 98%